PENGARUH STRUKTUR KEPEMILIKAN, LEVERAGE, PERTUMBUHAN PERUSAHAAN DAN EFEKTIVITAS USAHA TERHADAP KEBIJAKAN DIVIDEN - Rusli, Erik; Sudiartha, Gede Merta (E-Jurnal Manajemen, 2017)
This study aims to determine the effect of ownership structure, leverage, corporate growth and business effectiveness on dividend policy. This study was conducted on companies listed on the Indonesia Stock Exchange (IDX) in the period 2011-2015. The number of samples taken is as many as 8 companies. Method of sampling in this research use purposive sampling that is sample drawn a certain amount of population by using certain consideration or criteria. Methods of data collection is done through non-behavioral observation and using multiple regression analysis techniques. The results of this study indicate that Ownership Structure has a positive and significant effect on dividend policy. Leverage has a negative and significant effect on dividend policy. The company's growth rate has a negative and significant effect on the dividend policy. Business effectiveness has a positive and significant effect on dividend policy. Coefficient of determination total of this research is equal to 0,797 which mean dependent variable influenced by 79,7% by independent variable and the rest 20,3% influenced by variable outside model.